4-Amino pyrimidine derivatives: design, synthesis, antiviral, and antibacterial investigation - M. Aburzeza, Moktar; M. Awheda, Ismail; A. Kollab, Wesam; O. Abdulnnour, Alkhansa (Journal of Neonatal Surgery, 2025)
Numerous novel 4-Amino-pyrimidine-5-carbonitrile, 1,3-thiazine, and 1,3,4-thiadiazole derivatives were produced using 2-pyridin-4-ylmethylene) hydrazine-1-carboximidamide as the main starting material. In vitro tests were used to evaluate antiviral and antibacterial qualities. The synthesised compounds were characterised by elemental analysis, FT-IR, 1H NMR, and LC-MS spectral investigations.